Metakomunikasi dalam Fenomena Mengemis Online di Media Sosial Tiktok - Angga Tinova Yudha; An Nisa Dian Rahma; Syafruddin Pohan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to see how metacommunication in the phenomenon of online begging on TikTok social media. TikTok is one of the social media that is currently popular. Like other social media, TikTok should be used to interact virtually between one person and another. Researchers found the phenomenon of changes in meaning in the use of TikTok social media by several individuals. Some of the people in question use TikTok to beg online. This of course makes the meaning of social media change meaning. The problem is focused on the metacommunication that occurs on TikTok social media, which is currently found in many online begging phenomena. The method used in this research is descriptive qualitative using literature studies from several journals. This study concludes that metacommunication has occurred on TikTok social media where TikTok, which is known as a social media for interacting in cyberspace, has changed its meaning to become a place to carry out begging activities. The things that online begging actors do are dancing, sleeping in the garden and even taking a mud bath if someone gives a gift with various characters as a form of digital substitute for money with different amounts. Researchers also found that the mention of online begging activities with "Challenge Merchants" or "Non-Playable Character live streaming".